Chemical composition and biological activities of essential oils of the genus litsea (Lauraceae) a review - Muhammad Ammar Mohd Azhar (Tanjong Malim, 2020)
Chemical composition and biological activities of essential oils of the genus litsea (Lauraceae) a review by Muhammad Ammar Mohd Azhar